2011
DOI: 10.1179/037178411x12942393517291
|View full text |Cite
|
Sign up to set email alerts
|

Simulating fault slip areas of mining induced seismic tremors using static boundary element numerical modelling

Abstract: Two mining induced tremors that occurred in a South African deep-level gold mine are considered, with the aim to simulate the shear slip area and source mechanism using static boundary element numerical modelling. Large seismic tremors, induced by the extraction of the tabular ore body typically 1 m high over horizontal spans of kilometres, are a major seismic hazard in South African gold mines. For the cases considered here, virgin stress levels are y54 MPa, and seismic related damage is mainly due to geologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 4 publications
1
40
0
Order By: Relevance
“…As reported by Alber (2013), the magnitudes of strain bursts are generally less than 0; and the magnitudes of pillar bursts usually fall between 1.0 2 and 2.5. In contrast, seismic events induced by shear failure of rockmasses or fault reactivation have magnitudes greater than 2.5; occasionally the magnitude exceeds 4.0 (Alber, 2013;Hofmann & Scheepers, 2011), thus resulting in devastating damage to mine openings in a large area within underground mines.…”
Section: Résumémentioning
confidence: 99%
See 3 more Smart Citations
“…As reported by Alber (2013), the magnitudes of strain bursts are generally less than 0; and the magnitudes of pillar bursts usually fall between 1.0 2 and 2.5. In contrast, seismic events induced by shear failure of rockmasses or fault reactivation have magnitudes greater than 2.5; occasionally the magnitude exceeds 4.0 (Alber, 2013;Hofmann & Scheepers, 2011), thus resulting in devastating damage to mine openings in a large area within underground mines.…”
Section: Résumémentioning
confidence: 99%
“…Numerical analysis software, which employs finite difference methods (FDM), is used to simulate the behaviour of geological discontinuities (Cappa & Rutqvist, 2010;Hai-min, Yi-ming, & jun-gao, 2011;Zhi-hua, Lin-ming, Cai-ping, Zong-long, & An-ye, 2008). A boundary element method (BEM) is employed to simulate the areas of fault-slip that occurred in an underground mine, South Africa (Hofmann & Scheepers, 2011). Simon (1999) analyzed the behaviour of fault-slip in hard rock mines with BEM while applying a newly developed shear strength model.…”
Section: Simulation Methods Used For Fault-slip Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Liang et al used field test method to test the water pressure resistance of the normal fault and put forward the failure capacity index of unit seepage to reflect whether the fault activation occurred [14]. Based on the Mohr-Kulun failure criterion, Hoffman studied the variation law of the slip zone cohesive force when fault activation was unstable and concluded that the change of cohesion was the key to the activation of faults [15]. Zhang et al investigated the process of water inrush from fault caused by coal seam mining above the confined aquifer by physical simulation test and found that mining causes fault permeability enhancement, fault zone seepage flow from small to large which could be divided into three distinct phases, and the final fault generated activation of water inrush [16].…”
Section: State Of Artmentioning
confidence: 99%